Study and evaluation of correction factors applied to ionization chambers in radiotherapy photon beams - Reis, Cristiano Queiroz Melo dos (2015)
The use of a beam quality correction factor,kQ, is needed in dosimetry of radiotherapy beams for correcting differences between chamber responses at the calibration beam quality, Q0 and at the quality beam of the user, Q. The purpose of this study is to determine the beam quality correction factor for the NE2571 ionization chamber widely used in radiotherapy and its dependence with the stopping-power and the chamber perturbation factors. In addition, an investigation of the use of parallel plate chambers for determining surface doses in photon beams is also performed using the EGSrnc Monte Carlo code system. Results obtained with PENELOPE show that simulations with phase-space files appropriately scored can be up to ten times shorter than using a full spectrum in the input-file. Values of kQ, and its components show good agreement with published values in the literature and are provided with typical statistical uncertainties of 0.2%. Values of kQ and absorbed dose to water conversion factors obtained with egs_chamber user code for parallel plate chambers are also provided with maximum statistical uncertainty of 0.7%. Therefore, the results obtained are expected to contribute with improving dosimetry protocols and the quality of life of radiotherapy patients.